G‐CSF utilization rate and prescribing patterns in United States: associations between physician and patient factors and GCSF use. (20th November 2014) - Barnes, Gisoo; Pathak, Ashutosh; Schwartzberg, Lee
Abstract Febrile neutropenia (FN) is a common complication among patients with chemotherapy‐induced myelotoxicity and is associated with a number of negative outcomes including prolonged hospitalization, increased medical costs, increased risk of mortality, dose reductions, and delays. Granulocyte‐colony‐stimulating factor (G‐CSF), granulocyte–macrophage‐colony stimulating factor (GM‐CSF), and pegylated G‐CSF are effective at reducing risk and duration of neutropenia‐related events. However, despite guidelines, the use of G‐CSF and pegylated G‐CSF in the United States has not been consistent and pattern of care studies have focused primarily on G‐CSF. A number of studies found that G‐CSF is underutilized in patients undergoing chemotherapy treatments associated with a high risk of FN, while being over utilized in patients with a low‐risk FN. Wide variations in overuse, underuse, and misuse of G‐CSF are associated with a number of physician and patient factors. Improved awareness of the guidelines, feedback to providers regarding proper usage, and understanding of chemotherapy regimens associated with very low risks as well as high risks (>20%) of FN is some of the approaches that could lead to improving care.